A wider approach to aid effectiveness: Correlated impacts on health, wealth, fertility and education - David Fielding; Mark McGillivray; Sebastian Torres (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
In this paper we discuss the results of research into the impact of foreign aid on human development. Rather than focussing on per capita income, as is common in the existing literature, we look at how aid impacts on a range of human development indicators, including measures, of health, education and fertility, and allow for the fact that these different dimensions of wellbeing are likely to interact with each other. Overall, aid is found to have a substantial positive impact on many development outcomes. – aid ; health ; wealth ; fertility ; education
Keywords: O11; O15; 330; Entwicklungshilfe; Entwicklungsindikator